2014
DOI: 10.1186/1476-511x-13-67
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of colchicine combined with atorvastatin in rats with hyperlipidemia

Abstract: BackgroundInflammation and endothelial dysfunction is implicated in the atherosclerosis initiation and progression in the setting of hyperlipidemia. Colchicine is a potent anti-inflammatory agent and whether colchicine combined with atorvastatin has synergistic effects on inflammation amelioration and endothelial function improvement is unknown.MethodsHyperlipidemic rat model was produced by high-fat and high-cholesterol diet for 6 weeks. Rats with normal diet were served as shame group. In hyperlipidemic grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…In a rat pulmonary arterial hypertension model, colchicine suppressed smooth muscle cell proliferation, increased cell apoptosis and reduced protein expression of inflammation (TNF-a and NF-κB) [45]. Colchicine was shown to have synergistic protective effects with atorvastatin on endothelial function, reduced C-reactive protein (CRP) and lipoprotein associated phospholipase A2 (Lp-PLA2), and enhanced NO production in rats [46]. The clinical applications of colchicine in pericarditis and atherosclerosis have been under intense investigation.…”
Section: Resultsmentioning
confidence: 99%
“…In a rat pulmonary arterial hypertension model, colchicine suppressed smooth muscle cell proliferation, increased cell apoptosis and reduced protein expression of inflammation (TNF-a and NF-κB) [45]. Colchicine was shown to have synergistic protective effects with atorvastatin on endothelial function, reduced C-reactive protein (CRP) and lipoprotein associated phospholipase A2 (Lp-PLA2), and enhanced NO production in rats [46]. The clinical applications of colchicine in pericarditis and atherosclerosis have been under intense investigation.…”
Section: Resultsmentioning
confidence: 99%
“…And the mechanisms operating in these processes are partially dependent upon its detrimental roles on endothelial cells [2,3]. For example, Congwu Huang and colleagues reported that in rats with early stage of dyslipidemia, endothelium-derived nitric oxide (NO) generation, a sensitive and specific marker of endothelial function, was profoundly declined [4]. And atorvastatin therapy was beneficial for increased NO release and this benefit was partially attributable to dyslipidemia improvement by atorvastatin treatment [4].…”
mentioning
confidence: 99%
“…For example, Congwu Huang and colleagues reported that in rats with early stage of dyslipidemia, endothelium-derived nitric oxide (NO) generation, a sensitive and specific marker of endothelial function, was profoundly declined [4]. And atorvastatin therapy was beneficial for increased NO release and this benefit was partially attributable to dyslipidemia improvement by atorvastatin treatment [4]. Moreover, in humans with dyslipidemia, statins therapy promoted NO generation in accompany with cholesterol reduction [5][6][7][8].…”
mentioning
confidence: 99%
“…In animal models, colchicine has been shown to prevent the development of atherosclerosis and to reduce crystal-induced inflammation 43 44. Another interesting observation from animal studies revealed that colchicine works synergistically when combined with atorvastatin in reducing serum CRP and lipoprotein-associated phospholipase A2 (Lp-PLA2) levels and improving nitric oxide production in hyperlipidemic rat model 45. As inflammation and endothelial dysfunction play crucial roles in all stages of atherosclerosis, the synergistic effects of colchicine and statin on ameliorating vascular inflammation and improving endothelial function, if corroborated to produce similar benefits in humans, will be highly desirable in developing future therapeutic options in the management and prevention of cardiovascular disease.…”
Section: Colchicine In Cardiac Diseasesmentioning
confidence: 99%